VIABILITY OF PAYMENTS FOR ECOSYSTEM SERVICES PROVIDED BY THE LAQUIPAMPA WILDLIFE REFUGE, LAMBAYEQUE – PERU - Mercado, Waldemar (2023)
Natural protected areas and payments for environmental services are conservation mechanisms that lead environmental policies worldwide. Therefore, policymakers are faced with the choice of the effectiveness of conservation mechanisms and their evaluation of how to achieve this without compromising the well-being of the populations that live within those territories. The aim of this study was to evaluate the feasibility of implementing payment mechanisms for ecosystem services in the Laquipampa Wildlife Refuge. The methodology included the identification, evaluation, and economic valuation of the prioritized ecosystem services according to three criteria: contribution to the local economy, availability of information to carry out the economic valuation, and the plausibility of implementing activities regarding the objectives of the Master Plan. The results indicate that there is the possibility of implementing retribution for ecosystem services in the provision of tara pods (Caesalpinea spinosa) and recreational tourist services associated with the habitat of the white-winged guan (Penelope albipennis). Thus, it was estimated that the total economic value generated by these ecosystem services amounts to USD 12 389 per year and it is evident that it is possible to make remuneration mechanisms for ecosystem services viable in natural protected areas as long as there is a significant population of contributors and that the provision of goods is recognized by the market.